STRATEGY ANALYSIS FOR ACHIEVING SDGS TARGETS IN POSO REGENCY IN THE DEVELOPMENT OF THE TOMINI BAY ECONOMIC AREA - Sri Maryati; Harto S. Malik; Noval Sufriyanto Talani; Salahudin Olii (GeoEco, 2026)
Poso Regency has a highly strategic geopolitical position and a very high economic potential. However, in achieving sustainable development goals, there are several indicators whose progress is relatively slow. This research aims to map the general conditions of the region in achieving SDG indicators for Poso Regency, categorise the achievement of SDG indicators for Poso Regency, and identify regional strengths, weaknesses, opportunities, and challenges in achieving SDG indicators for Poso Regency. Data collection was conducted through the search of secondary data and the collection of primary data via interviews and questionnaires completed by stakeholders in Poso Regency. The data analysis technique chosen in this research is SWOT analysis. The research results indicate that Poso Regency has greater strengths than weaknesses in achieving poverty indicators and gross regional domestic product (GRDP) growth rates. Poso Regency has greater opportunities than threats in achieving the SDGs' poverty indicators and GRDP growth rates. Poso Regency shows advantageous conditions in achieving poverty indicators and economic growth rates by maximising its strengths and opportunities. Efforts to reduce poverty rates and increase the GRDP of Poso Regency can be implemented through integrated and sustainable programs involving various relevant stakeholders.